The Role of Investment Opportunity Set in Earnings Growth - Ubaidillah, Moh.; Novitasari, Maya (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study aims to determine the effect of capital structure on earnings growth with Investment Opportunity Set as a moderating variable. The population of this study consists of Consumer Cyclicals and Non-Cyclicals companies listed on the Indonesia Stock Exchange from 2020 to 2022, totaling 255 companies. The sample of this study used 131 Consumer Cyclicals and Non-Cyclicals companies with the data collection method using purposive sampling. Financial data processed as many as 393 of the 131 companies. This study conducted outlier data because it was not normal, the remaining data to be processed was 271 financial data. This research analysis technique uses linear regression with SPSS 24. The results of this study indicate that the capital structure variable has no effect on earnings growth. Investment Opportunity set variable has no effect on earnings growth. Then the Investment Opportunity Set variable as a moderating variable is not able to moderate the effect of capital structure on earnings growth. The capital structure is financial in nature, while profit growth comes from operational and strategic activities. Even if a company has high leverage, if its operations are poor, profits will not grow. This is what makes the capital structure irrelevant. To increase profit growth, companies need an Investment Opportunity Set to support smooth operations and strategies. However, the Investment Opportunity Set cannot moderate this because this variable has too strong a direct effect on profit growth.